Association of the geriatric nutritional risk index with mortality in patients with rheumatoid arthritis - Zhong Wen; Shunbing Wang; Yuzhi Li; Xin Tu; Quanbo Zhang; Yufeng Qing (Medicine, 2026)
To investigate the association of the geriatric nutritional risk index (GNRI) with all-cause and cardiovascular mortality among adults with rheumatoid arthritis (RA). Data were obtained from the National Health and Nutrition Examination Survey 2007 to 2018. The GNRI was evaluated continuously and categorically (< 98 vs ≥ 98). Survey-weighted Cox proportional hazards models were used to estimate hazard ratios and 95% confidence intervals (CIs) for all-cause and cardiovascular mortality. Restricted cubic spline, competing-risk, subgroup, and sensitivity analyses were conducted as secondary analyses. Participants with RA had a lower GNRI than those without RA (102.7 vs 105.1; P < .001) and higher all-cause (10.0% vs 6.6%) and cardiovascular mortality (2.7% vs 1.5%). In the fully adjusted model, higher GNRI was associated with a lower risk of all-cause mortality (hazard ratio per 1-unit increase, 0.94; 95% CI, 0.89–1.00; P = .032). Participants with a GNRI .05). A lower GNRI was associated with higher all-cause mortality among participants with RA and may help identify individuals at increased risk. Further prospective studies are needed to determine whether the GNRI provides clinically useful risk information beyond established prognostic factors.